Т.МӘТМУРАТОВТЫҢ ВУЛЬГАРИЗМЛЕРДЕН ПАЙДАЛАНЫЎЫ - Бухарбаева, Ж.Ж. (ILIM hám JÁMIYET, 2022)
The article studied the and methodological application of vulgarisms used in the works of the poet T.Matmuratov. Also, the poet's works studied the attitude of vulgarism to the events and events of the characters.